ОБЕСПЕЧЕНИЕ ГЕНДЕРНОГО РАВЕНСТВА КАК ВАЖНОЕ НАПРАВЛЕНИЕ РЕФОРМ В СОВРЕМЕННОМ УЗБЕКИСТАНЕ - Сеитова, З.П. (SCIENCE and SOCIETY, 2025)
In the article the author examines issues of gender equality. How are these issues resolved at the state level? An analysis of sources that covered equality issues in their publications is carried out. And now this issue is at the state level.